The Right to Know: What, When and for How Long. Appraisal and Selection in the Information Age? - Jeurgens, Charles (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
The Article discusses some of the recent developments in information management by government institutions in the Netherlands from an archival perspective. It aims to answer the following questions: How to master the flood of information, especially in the digital era? How to keep relevant and important information available and accessible to citizens? One of the specific problems within the realm of information management by government institutions is appraisal and selection of information. How to decide which information should be available and accessible for how long, and how to decide which information should become part of the ‘historical memory’ and kept accessible forever? What are the big challenges we need to tackle with respect to the issue of appraisal and selection in the digital information society?
Keywords: Holandia; zarządzanie informacją